Photocatalytic coupling of formaldehyde to ethylene glycol and glycolaldehyde over bismuth vanadate with controllable facets and cocatalysts. Issue 4 (2nd February 2017) - Xie, Shunji; Shen, Zebin; Zhang, Huamin; Cheng, Jun; Zhang, Qinghong; Wang, Ye
Abstract : Bismuth vanadate single crystals with controllable facets and cocatalysts show excellent performance for photocatalytic coupling of formaldehyde into C2 compounds. Abstract : Bismuth vanadate (BiVO4 ) single crystals with controllable facets and cocatalysts were synthesized and studied for photocatalytic coupling of formaldehyde into C2 compounds mainly including ethylene glycol and glycolaldehyde. By using chloride anions as a morphology-controlling agent, we succeeded in synthesizing BiVO4 single crystals with a uniform truncated tetragonal bipyramidal morphology enclosed with {010} and {110} facets. The ratio of exposed {010} and {110} facets could be regulated by changing the concentration of Cl − . BiVO4 with an equal fraction of exposed {010} and {110} facets exhibited the highest capability of electron–hole separation and the highest C2 -compound yield. The loading of core–shell structured Pt@MoO x and MnO x particles onto {010} and {110} facets, respectively, further enhanced the formation of C2 compounds. Our studies suggested that the Pt core and the MnO x particles accelerated the separation of photogenerated electron–hole pairs, whereas the MoO x shell catalyzed the coupling of HCHO possibly via a redox mechanism. The yields of C2 compounds and ethylene glycol reached 21% and 11%, respectively, under irradiation with UV-vis light for 12 h. Quantum yields of 11% and 4.8% were achieved for the coupling products under ultraviolet (350 nm) and visible (450 nm) light irradiation, respectively.